(untitled) (Libellarium: journal for research in the field of information and related sciences, 2018)
The written production of Croats in Hungary so far has only been partially collected, recorded and bibliographically processed. This shortcoming is attempted to be compensated by several researches that intend to collect and process Croatian publications published from the end of the First World War to 2015. The aim of this paper is to describe the connection between the Croatian written word and the formation of various social / collective identities. the national identity of the Croatian community in Hungary in the last 100-150 years. Referring to many studies, we can say that the printed word has played a crucial role in shaping society in recent centuries. The spread and more efficient distribution of printed products is associated with movements such as the Reformation, various revolutions that greatly affected society, radically changed relations within communities. In addition, most researchers dealing with the processes of emergence of various collective identities, e.g., modern national communities (B. Anderson, E. Gellner, A. D. Smith, J. Assmann, etc.), give key importance to the spread of printed products. In the mentioned period, books are printed, various periodicals are published in the Croatian language and, we assume, these editions reach their readers. This paper will identify those collective value systems whose presence has been confirmed among Croats in Hungary, describe why the written word plays an important role in building social identities, and confirm the persistence of such identities on the pages of Croatian print media in Hungary.